BioInspired, BioDriven, BioMADE: The U.S. Bioindustrial Manufacturing and Design Ecosystem as a driver of the 4th Industrial Revolution. Issue 3 (13th September 2021) - Rose, Patrick P.; Friedman, Douglas
Abstract: When we think about the potential that biology has to offer, the U.S. Bioindustrial Manufacturing and Design Ecosystem or BioMADE slogan could read, 'we don't make the products you buy, we make the products that you buy, with biology'. BioMADE is a non‐profit public–private partnership between the U.S. government and the private sector to leverage the work already accomplished in industry, accelerate the bioindustrial revolution, and create a stronger, resilient, sustainable, and environmentally friendly manufacturing ecosystem. BioMADE endeavours to be a leader, an enabler, and a beacon for how contemporary manufacturing can be transformed with biology to mature the bioindustrial manufacturing ecosystem. The institute cannot go this path alone to solve all the problems and coalesce the existing ecosystem. It requires determination and commitment from the private sector, academia, non‐profit research institutions and national laboratories; the entire community. Many technical challenges and adoption hurdles still loom high. Industry and consumers need to start accepting that engineering biology has a critical role to play in the manufacturing of many of the materials and products we use today.